The Relationship of Fat Intake and Body Fat Percentage in Medical Students - Nurul Yuli Permata Sari; Ardesy Melizah Kurniati; Julius Anzar; Liniyanti D. Oswari; Sri Nita; Syarinta Adenina (Biomedical Journal of Indonesia, 2024)
Introduction. Obesity is an excessive fat accumulation in the body, now the prevalence is increasing in the group aged>18 years based on Body Mass Index (BMI). Nowadays body fat percentage has been declared to assess the risk factor of disease-related body weight better than BMI, people with proportioned weight had excessive body fat percentage evenly. Excessive fat intake is one of the important factors for obesity. The objective of this study was to analyze the association between fat intake with body fat percentage. Methods. This study was conducted with a cross-sectional design on 275 medical faculty students of Sriwijaya University, starting from August until December 2017 by collecting primary data through completing forms, food records, questionnaires, and physical examinations. Results. The results were analyzed statistically using chi-square. 67.3% of subjects had excessive body fat percentage and 50.2% with excessive fat intake. Results by the chi-square test indicate a negative association between fat intake with body fat percentage (p value=0.184). Conclusion. Fat intake with body fat percentage was negatively associated.